The place and the efficacy of infectious disease consultations in the hospitals - (:unkn) unknown (My University, 2012)
Our study aims to determine the efficacy of infectious disease consultations and the interrelations between doctors in this social laboratory. This study was conducted at 34 centers located in 22 cities across Turkey and contributed by 210 infectious disease specialists (IDSs) and 970 non-infectious disease specialists (NIDSs), totaling 1180 medical doctors. Infectious disease specialists and NIDSs have separately contributed by responding to questionnaires designed specifically for the consultation process. It appears that a satisfactory collaboration has been established between IDSs and NIDSs during the consultation practices. There are some discrepancies in the perceptions of some of the NIDSs. These are the evaluation of patients holistically, the expectation of NIDSs in critical infection cases to start the therapy immediately, losing the support of drug companies by NIDSs, and the restriction of NIDSs in routine medical practice. On the other hand, NIDSs seem to have real problems in the diagnosis or treatment of infectious diseases. The consultation service provided by the IDSs in Turkey is widely accepted among other clinicians and appears to be of a crucial importance. Copyright © 2012 by Lippincott Williams & Wilkins.
Keywords: consultation; hospitals; Infectious diseases